Aesthetic labouring and the female entrepreneur: 'Entrepreneurship that wouldn't chip your nails'. (June 2019) - Pritchard, Katrina; Mackenzie Davey, Kate; Cooper, Helen
Recognising significant interrelations between neoliberal and postfeminist discourses, we advance understandings of constructions of female entrepreneurs by unpacking their visual representation and exploring the role of aesthetic labour. Given the impact of contemporary media, we focus on key images integral to the marketing of Mattel's Entrepreneur Barbie as a postfeminist cultural icon and investigate how these representations of female entrepreneurship are consumed. First, we highlight the practical demands and emotional risks of the aesthetic labour required to achieve such postfeminist glamour. Second, links between conventional femininity and entrepreneurial success are both celebrated and challenged, highlighting perceived limits to achievement. Finally, we unpack understandings of the relations between entrepreneurialism and aesthetic labour to move beyond assumptions of the instrumental power of the makeover. Our findings thus enrich understandings of the consumption of postfeminist images of entrepreneurs.